2018
DOI: 10.1155/2018/6236270
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic Lymphohistiocytosis Associated with Salmonella typhi Infection in a Child: A Case Report with Review of Literature

Abstract: We present the case of an 8-year-old girl with hemophagocytic lymphohistiocytosis secondary to a Salmonella typhi infection. She received antibiotic treatment and intravenous immunoglobulin with complete resolution of the symptoms. We present a review of previously reported pediatric cases and propose a gradual approach to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The most common cause of IAHS in developed countries was EBV infection 31 followed by other viruses, that is, CMV and herpes simplex virus 32 . On the contrary, tropical infections, that is, Salmonella spp., 33 dengue virus, 14,29 malaria, 13 and Leishmania spp 34 . were predominantly addressed in developing countries as in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of IAHS in developed countries was EBV infection 31 followed by other viruses, that is, CMV and herpes simplex virus 32 . On the contrary, tropical infections, that is, Salmonella spp., 33 dengue virus, 14,29 malaria, 13 and Leishmania spp 34 . were predominantly addressed in developing countries as in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 8 ] To the best of our knowledge, there are six cases of sHLH as a complication of typhoid fever by S. typhi reported in the pediatric population. [ 9 ] Thorough literature search did not reveal similar case with rare associations of this dual complication of meningitis and hemophagocytosis in the same patient. In our case, salmonellosis presented with HLH as a primary complication followed by meningitis later on.…”
Section: Discussionmentioning
confidence: 90%
“…Navneet et al reported a sHLH patient triggered by S.typhi was treated by ceftriaxone along with supportive care [11]. Juanita Uribe-Londono et al reported a sHLH patient triggered by S.typhi was treated by piperacillin-tazobactam, intravenous immunoglobulin, and cipro oxacin, who completed 14 days of antibiotic treatment and discharged from hospital [12]. Arslansoyu Çamlar et al reported an early diagnosis of S.typhi, treatment with parenteral ceftriaxon and supportive treatment prevented progression of HLH [13].…”
Section: Discussionmentioning
confidence: 99%